HUBUNGAN PENGETAHUAN IBU TENTANG IMUNISASI DASAR DENGAN KELENGKAPAN IMUNISASI DASAR PADA BAYI DI DESA KARANGSARI KECAMATAN KEBASEN KABUPATEN BANYUMAS - Etika Dewi Cahyaningrum; Risna Dewi Rohmadoni (Universitas Harapan Bangsa Purwokerto, 2012)
Background : Every year in all the world, hundreds of mother, adult and childrendie because disease which in fact admit of to be prevented. This matter because oflack of information about is important of immunize. Immunize to represent one ofthe way of prevention of serious infection disease which most effective of itsexpense. Knowledge of old fellow represent factor which is very have an effect onso that can improve awareness for the importance of activity immunize to childgrowth. Result of antecedent study in Region Countryside Karangsari from 10raised statement to 10 responder, only 4 people ( 40%) able to answer more than5 statement and incomplete there is 2 baby.Target of : To know relation between knowledge of mother about immunizingbase with equipment immunize base at baby in Countryside Karangsari District ofKebasen Sub-Province Banyumas year 2011.Method : This Research is descriptive research of correlation with approach ofsectional cross. total used Sampel ofsampling, this research sampel of motherhaving baby amount to 66 responder, kuesioner instrument, data analysis usesquere chi.Result of : Most knowledge of mother about immunizing base enough counted 36responder (54,5%), most complete responder in immunize base counted 51responder (77,3%), there is relation knowledge of mother about immunizing basewith equipment immunize base at baby with x value count > x of[is tables of(28,212 > 5,991).Conclusion : There is relation knowledge of mother about immunizing base withequipment immunize base at baby. Keyword : Knowledge, Immunize Base, Equipment, Baby.